Twelve steps for family medicine remote consultations: one pandemic times adaptation - Gomes, Ana Catarino (2022)
This article proposes a structure for family medicine remote consultations, exploring strategies to overcome communicational barriers. The authors propose twelve steps divided into three phases. Phase I. Preparation. Step 1. Place choice: evaluate room conditions. Step 2. Connection verification: verify telephone, computer, and printer availability and the presence of a good internet connection. Step 3. Room preparation: make sure there is good lighting and that all objects you may need are properly placed. Step 4. Organizing ideas: read the previous medical records and any important alerts. Phase II. Remote consultation. Step 5. Sessions make ready: make sure you have the correct patient’s contact, session passwords as well as the computer’s department helpline number. Step 6. First minutes: make sure video and sound are working correctly; confirm patient’s identification and ensure privacy. Step 7. Quick assessment: quick assessment if the patient is severely ill or not; if severe illnesses, write a short anamnesis and assess vital signs in order to decide whether or not to send the patient to seek medical attention. Step 8. Exploration: present illness anamnesis. Step 9. Evaluation: this is the most complex step; patient descriptions, live video images or emailed afterward, measurements with patient’s medical devices, and the use of various medical scales are of great help. Step 10. Decision: gathering all the information in other to manage the correct follow-up procedures with patients’ agreement. Phase III. Final. Step 11. Closure: make sure that all topics were discussed, and that the patient understands the plan. Step 12: Final reflection: medical records should be finished and a doctor’s self-reflection on the consultation should take place. For breaking bad news SPIKES protocol should be used. This article was thought of as a consultation guide for family medicine remote consultations in order to improve doctors’ approach during the COVID-19 pandemic.